Occupational Risk: Needle-Stick Injuries and Its Determinants Among the Healthcare Workers - Ghimire, Madhusudan; Sharma, Achala; Poudel, Anuj; Ghimire, Moushami (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Needle-stick injuries are common problems among the healthcare workers; it might impact significantly on workers' health and health care delivery services. Sometimes small pinch of infected needle or sharp instrument may lead to big threat in their life and it may go into mortal outcomes.OBJECTIVE: To explore prevalence of needle-stick injuries and its determinants among the healthcare workers in Banke, Pyuthan and Palpa district of Nepal.MATERIALS & METHODS: A cross-sectional study was undertaken in 2015 and that focused on needle-stick injuries and its determinants. Data were collected by using an unstructured pre tested questionnaire from 359 healthcare workers. SPSS-21 windows process was used to analyze the information. RESULTS: Three hundred fifty-nine health care workers: Doctors (23.70%), Allied health workers (37.60%), Nurses (31.80%), and Laboratory staffs (7.00%) were involved in the study. The mean age of health workers was 32.75 ± 10.478 years. 37.60% of total healthcare workers had needle stick injuries.CONCLUSION: The prevalence of needle-stick injuries was associated strongly with age of healthcare workers, depression, social problems and alcohol consumer and, practice of sleepJournal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, page : 45-48